Experimental analysis of sequential water alternating CO₂ gas injection for enhancing oil recovery in X-field sandstone reservoir of Cambay basin - Ashutosh Rawat; Bhaskarjyoti Khanikar; Abhishek Kumar Samanta; Patrick Nguessan; Bhavesh Mehta; Anirbid Sircar; Bhawanisingh Desai; Achinta Bera; Namrata Bist (Scientific Reports)
Abstract This study evaluates the oil recovery potential of sandstone reservoirs through sequential water-alternating CO₂ gas injection. Experimental work focuses on optimizing injection patterns, including alternating CO₂ and water cycles, to assess their impact on enhanced oil recovery (EOR). Analytical methods performed before detailed analyses include Fourier Transform Infrared (FTIR) Spectroscopy and X-ray diffraction (XRD) on the crude oil and core samples from the same field of Cambay Basin. FTIR analysis revealed a dominance of long-chain aliphatic hydrocarbons, suggesting favorable interactions with CO₂ for viscosity reduction and oil swelling. XRD revealed quartz-dominant cores with subordinate feldspar that control fluid permeability and chemical interactiveness. Sequential Water-Alternating-Gas (WAG) injection improved sweep efficiency by minimizing gas channeling and maximizing CO₂-oil contact. Soak periods conducted during injection enhance some miscibility effects with addition of extra oil mobility. High permeability cores experienced early gas breakthroughs, while low permeability delayed gas movement, achieving better recovery. Reservoir heterogeneities and water-shielding effects were critical challenges, underscoring the role of petrophysical properties in recovery performance. The results demonstrate that CO₂ WAG injection in sandstone reservoirs significantly enhances crude oil recovery by improving oil displacement efficiency. The presented work emphasizes the parameters porosity, permeability, and oil saturation as prerequisites for the process. Collected sandstone core samples show that variations in these properties influence the effectiveness of CO₂ WAG injection showing the resultant oil recovery increase by 20–25% after secondary brine injection. The integration of advanced characterization and strategic injection patterns establishes a foundation for optimizing CO2 EOR in mature fields.